Vegan Diet, Subnormal Vitamin B-12 Status and Cardiovascular Health - Woo, Kam S. (MDPI, 2014)
Vegetarian diets have been associated with atherosclerosis protection, with healthier atherosclerosis risk profiles, as well as lower prevalence of, and mortality from, ischemic heart disease and stroke. However, there are few data concerning the possible cardiovascular effects of a vegan diet (with no meat, dairy or egg products). Vitamin B-12 deficiency is highly prevalent in vegetarians; this can be partially alleviated by taking dairy/egg products in lact-ovo-vegetarians. However, metabolic vitamin B-12 deficiency is highly prevalent in vegetarians in Australia, Germany, Italy and Austria, and in vegans (80%) in Hong Kong and India, where vegans rarely take vitamin B-12 fortified food or vitamin B-12 supplements. Similar deficiencies exist in northern Chinese rural communities consuming inadequate meat, egg or dairy products due to poverty or dietary habits. Vascular studies have demonstrated impaired arterial endothelial function and increased carotid intima-media thickness as atherosclerosis surrogates in such metabolic vitamin B-12 deficient populations, but not in lactovegetarians in China. Vitamin B-12 supplementation has a favourable impact on these vascular surrogates in Hong Kong vegans and in underprivileged communities in northern rural China. Regular monitoring of vitamin B-12 status is thus potentially beneficial for early detection and treatment of metabolic vitamin B-12 deficiency in vegans, and possibly for prevention of atherosclerosis-related diseases.